Individual changes of central blood pressure in response to upright posture: different hemodynamic phenotypes. Issue 12 (December 2021) - Suojanen, Lauri J.; Koskela, Jenni K.; Wilenius, Matias; Choudhary, Manoj Kumar; Hautaniemi, Elina J.; Viik, Jari; Mustonen, Jukka T.; Pörsti, Ilkka H.
Abstract : Objectives: Most studies about upright regulation of blood pressure have focused on orthostatic hypotension despite the diverse hemodynamic changes induced by orthostatic challenge. We investigated the effect of passive head-up tilt on aortic blood pressure. Methods: Noninvasive peripheral and central hemodynamics in 613 volunteers without cardiovascular morbidities or medications were examined using pulse wave analysis, whole-body impedance cardiography and heart rate variability analysis. Results: In all participants, mean aortic SBP decreased by −4 (−5 to −3) mmHg [mean (95% confidence intervals)] and DBP increased by 6 (5--6) mmHg in response to upright posture. When divided into tertiles according to the supine-to-upright change in aortic SBP, two tertiles presented with a decrease [−15 (−14 to −16) and −4 (−3 to −4) mmHg, respectively] whereas one tertile presented with an increase [+7 (7-- 8) mmHg] in aortic SBP. There were no major differences in demographic characteristics between the tertiles. In regression analysis, the strongest explanatory factors for upright changes in aortic SBP were the supine values of, and upright changes in systemic vascular resistance and cardiac output, and supine aortic SBP. Conclusion: In participants without cardiovascular disease, the changes in central SBP during orthostatic challenge are not uniform. One-third presented with higher upright than supine aortic SBP with underlying differences in the regulation of systemic vascular resistance and cardiac output. These findings emphasize that resting blood pressure measurements give only limited information about the blood pressure status. Abstract : Supplemental Digital Content is available in the text